Ações de educação em saúde para prevenção da COVID-19 por meio da utilização de mídias sociais - Souza, Jamires Silva de (Brasil, 2023)
The virus (Sars-CoV-2) causes the most recent disease characterized as a threat to global health and mainly has a course of respiratory disease. The main symptoms can be fever, cough and dyspnoea and the risk may increase with age and the presence of other associated diseases in the patient. Currently, treatment is supportive and vaccination is the most effective method of combating the virus, but, given the still limited number of vaccines in the world, it is still necessary to continue preventive measures, preventing the virus from spreading, thus protecting way, yourself and others. Most global strategies for responding to the fight against this disease include various levels of contact screening and self-isolation or quarantine, which are the best forms of prevention and also the way to prevent further spread of the virus. Due to social isolation for disease prevention, one of the alternatives that can be used to provide information based on health education to the general population is through the mass media. Thus, the objective of this work was to use social networks as a tool to raise public awareness in relation to the prevention of COVID-19, in order to offer and facilitate access to educational information. The disclosure of the information occurred through daily posts through the @educacaoesaude_medvet profile of the social network Instagram®, which contributed to the presentation of satisfactory results related to the online questionnaire prepared in Google Forms, with questions on the following points: new coronavirus (SarsCoV-2) and disease (COVID-19) and the role of communication channels in the dissemination of true and false information. Which resulted in a total of 278 responses reaching an audience from all Brazilian states, with 80% of the participants residing in Manaus-AM. The filling was anonymous and voluntary, qualitative and quantitative in terms of the content and information conveyed inherent to the disease. This work resulted in the publication of a scientific article for the academic community, in the journal Archives of Veterinary Sciences and Zoology of University Paranaense-UNIPAR. Given the importance of the theme, it is necessary to continue this project through health education actions with the dissemination of health information, sources with true information, booklets and daily publications to reach a greater number of individuals and thus contribute to the formation of critical awareness. about the disease and maintaining its prevention.